Effect of atropine 0.01% on myopia control in children aged 6–13 years during the 2022 lockdown in Shanghai - Yu, Manrong; Jiang, Lingli; Chen, Minjie (Frontiers in Public Health, 2023)
Purpose To compare the myopic progression in children treated with 0. 01% atropine and those who discontinued atropine during the 2022-home quarantine in Shanghai. Methods In this retrospective study, children aged 6–13 years with follow-up visits before (between January 2022 and February 2022) and after the lockdown (between July 2022 and August 2022) were included. Cycloplegic refraction and axial length (AL) were measured at both visits. The atropine group had continuous medication during the lockdown while the control group discontinued. The 0.01% atropine eyedrops were administered daily before bedtime. The types of spectacle lens were recorded: single vision (SV) spectacles or defocus incorporated multiple segments lenses (DIMS). Results In total, 41 children (81 eyes) in the atropine group and 32 children (64 eyes) in the control group were enrolled. No significant difference was found in the demographic characteristics, spherical diopter, spherical equivalent (SE), AL, and follow-up time between the two groups before the lockdown in 2022 (all p > 0.1). After the home confinement, a greater myopia progression was observed in the control group (−0.46 ± 0.42 D) compared to atropine group (−0.26 ± 0.37 D; p = 0.0023). Axial elongation was also longer in the control group than that in children sustained with atropine (0.21 ± 0.17 vs. 0.13 ± 0.15 mm, p = 0.0035). Moreover, there was no significant change of spherical diopter and SE during lockdown in the atropine + DIMS combined subgroup (0.03 ± 0.033 D for spherical diopter, p = 0.7261 and 0.08 ± 0.27 D for SE, p = 0.2042, respectively). However, significant myopic shift was observed in the atropine + SV subgroup during the quarantine time (−0.31 ± 0.39 D for SE and 0.15 ± 0.16 mm for AL, both p < 0.001). Conclusion Children treated with 0.01% atropine had slower myopia progression during the lockdown period in Shanghai compared with children discontinued. Moreover, the effect of atropine on myopic prevention can be strengthened with DIMS lenses.